State Surveillance, Political Policing and Counter-Terrorism in Britain : 1880-1914. - Solomon, Vlad. (Melton : Boydell & Brewer, Incorporated, 2021)
The formation of state surveillance and the emergence of institutionalized political policing in late Victorian and Edwardian Britain.
Introduction; Prologue; 'A spider's web of Police Communication'; 'Panic and indifference'; Mr Jenkinson goes to London; 'The new detective army'; 'Waiting games'; 'A long and complicated inquiry'; The Battle of Trafalgar Square; Scandal Averted; 'A bomb has burst'; 'Men of bad character'; 'Surtout pas trop de zèle'; 'We do not prosecute opinions'; Dangerous Aliens; 'A doctrine of lawlessness'; 'Suffrage forces in the field'; The Waning of Militancy and the Rise of Counter-espionage; Conclusion; Bibliography; Index
Description based upon print version of record.
JSTOR
Keywords: Intelligence service -- Great Britain -- History -- 19th century; Intelligence service -- Great Britain -- History -- 20th century; Terrorism -- Great Britain -- Prevention -- History -- 19th century; Terrorism -- Great Britain -- Prevention -- History -- 20th century; Terrorisme -- Grande-Bretagne -- Prévention -- Histoire -- 19e siècle.; Terrorisme -- Grande-Bretagne -- Prévention -- Histoire -- 20e siècle.; Intelligence service; Terrorism -- Prevention; Great Britain; 1800-1999; Electronic books; History